Spatial Analysis of Perceived Logistics and Traffic Impacts from Chinese Tourists on Nimmanaheaminda Residents - Chamaiporn Roongsaprangsee; Pairach Piboonrungroj (International Journal of Supply Chain Management, 2016)
This study aims to assess the perceived logistics and traffic impacts of Chinese tourists in Nimmanahaeminda, Chiang Mai, Thailand. This paper focus on the spatial analysis of residents attitude about these issues by investigating each tract of Nimmanahaemindas area. Quantum Geographic Information System (QGIS) was employed to illustrate the perception of residents on the logistics and traffic impact influenced by Chinese tourists. Moreover, this study also used Structural Equation Model (SEM) to estimate overall logistics and traffic impacts of the community in order to demonstrate the current situation for the government and other administrations to find the solution together.